The reasons and consequences of social shocks in the Arab countries at the beginning of the XXI century (ҚазҰУ хабаршысы. Шығыстану сериясы, 2016)
The paper discusses social processes in the countries of North Africa and the Middle East at the beginning of the XXI century.
Keywords: «the Arab spring»; reasons; consequences; Arabic countries; West countries.